A test of the standard dark matter density evolution law using galaxy clusters and cosmic chronometers - Bora, Kamal; Holanda, R. F.L.; Desai, Shantanu; Pereira, S. H. [UNESP] (Springer Nature, 2022)
In this paper, we implement a test of the standard law for the dark matter density evolution as a function of redshift. For this purpose, only a flat universe and the validity of the FRW metric are assumed. A deformed dark matter density evolution law is considered, given by ρc(z) ∝ (1 + z) 3+ϵ, and constraints on ϵ are obtained by combining the galaxy cluster gas mass fractions with cosmic chronometers measurements. We find that ϵ= 0 within 2σ c.l., in full agreement with other recent analyses.